DC Sputtered Ultralow Loading Gold Nanofilm Electrodes for Detection of As (III) in Water. (19th May 2022) - Casuse, Tybur Q.; Benavidez, Angelica; Plumley, John B.; Tsui, Lok-kun; Ali, Abdul-Mehdi; Cerrato, José M.; Garzon, Fernando H.
Abstract : This study investigates the use of DC sputtering, physical vapor deposition as a facile method for creating ultralow loading, Au/C electrodes for use in the detection of As (III) in water. The sputtered nanofilm electrodes on carbon papers, substantially reduces the amount of Au consumed per electrode, <10 μ g cm −2, compared to use of wire, foil, or screen-printed electrodes. Linear stripping voltammetry (LSV) was chosen for analytical simplicity and ease of automation. Electrodes using Au nanoparticles supported on Vulcan XC 72 R carbon were also investigated but were not viable for LSV analysis due to capacitive current charging of the high surface area carbon. The DC sputtered, Au nanofilm electrodes were used to create calibration curves for concentrations of As (III) between 5 and 50 μ g l −1 and the standard addition method was used in a surface water sample with 5.5 μ g l −1 total As. Peak areas plotted against concentration displayed strong linear correlation with meaningful detection below the USEPA maximum contaminant level (MCL) of 10 μ g l −1 . To our knowledge, this is the first study which utilizes the facile and mass manufacturable DC sputtering method to produce As (III) sensing electrodes. The results of this study have implications for the development of single use, low-cost nanofilm electrodes for field As (III) electroanalysis.